THE EFFECTIVENESS OF CHEST COMPRESSION EXERCISE USING THE “CPR TRAINER” APPLICATION BASED ON ANDROID ON THE SPEED OF DOING CHEST COMPRESSIONS STUDY ON A MANEKIN - Setianingsih Setianingsih; Lestari Eko Darwati; Naimatur Rizkiyah; Ahmad Asyrofi (Universitas Airlangga, 2022)
Introduction: The problem of cardiac arrest is currently the number one cause of death in the world so that fast treatment is needed, namely cardiopulmonary resuscitation (CPR). Nursing students are prospective health workers who must have basic skills in performing CPR, but most have not been able to perform chest compressions at the right speed. Achieving these abilities requires an appropriate learning media, one of which is by using the